1965
DOI: 10.1002/jobm.19650050108
|View full text |Cite
|
Sign up to set email alerts
|

Geomikrobiologische Untersuchungen. IV. Untersuchungen über die mikrobielle Verwitterung von Kalkstein im Karst

Abstract: Eingegayptt u t t i 20. 7. 61) I. EinleitungDie Entstehung der Karst -Topographic, insbesondere auch der charakteristischen Kleinformen der Verwitterung, ist oft untersucht worden. Unter den biotischen Faktoren, die an der Verwitterung beteiligt sind, haben in erster Linie die mechanischen und biochemischen Wirkungen Beachtung gefunden, die von wachsenden Pflanzenivurzeln ausgehen. Von Mikroorganismen war es vor allem die erste Besiedlung des Kalksteins durch epilithische und endolithische Flechten und Cyanoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1966
1966
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…These oxidation processes result in the production of nitrous and nitric acid. Several studies revealed the participation of nitrifying bacteria in rock and soil mineral weathering (Wagner and Schwartz 1965;Faurie 1977;Lebedeva et al 1978;Berthelin et al 1985). Many more studies dealt with the role of nitrifying bacteria in the biodeterioration of building stone (e.g., Krumbein 1968;Sand and Bock 1991;Bock and Sand 1993;Mansch and Bock 1998;Warscheid and Braams 2000).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…These oxidation processes result in the production of nitrous and nitric acid. Several studies revealed the participation of nitrifying bacteria in rock and soil mineral weathering (Wagner and Schwartz 1965;Faurie 1977;Lebedeva et al 1978;Berthelin et al 1985). Many more studies dealt with the role of nitrifying bacteria in the biodeterioration of building stone (e.g., Krumbein 1968;Sand and Bock 1991;Bock and Sand 1993;Mansch and Bock 1998;Warscheid and Braams 2000).…”
Section: Introductionmentioning
confidence: 96%
“…In weathering studies pure cultures of Thiobacillus thiooxidans (re-named Acidithiobacillus thiooxidans, Kelly and Wood 2000) solubilized Si, Fe, and Al from karst limestone (Wagner and Schwartz 1965), and Ca, Fe, and Al from granite (Wagner and Schwartz 1967).…”
Section: Introductionmentioning
confidence: 99%
“…KAUFMANN (1952KAUFMANN ( -1960 beschaftigte sich speziell mit dem EinfluB der Sitrifizierer auf die Verwitterung, POCHON et aE. (1950)(1951)(1952)(1953)(1954)(1955)(1956)(1957)(1958)(1959)(1960)(1961)(1962)(1963)(1964) WAGNER und SCHWARTZ (1965-1967 haben in langfristigen Perkolatorversuchen mit verschiedenen Qesteinen und Gesteinsmineralien gezeigt, daB die gesteinsbesiedelnde Mikroflora die Losung von Na, K, Ca, Mg, Fe, A1 erheblich beschlennigt. Hierbei sind sowohl mikrobiell gebildete anorganische als auch organische SLuren und wahrscheinlich auch chelatbildende Substanzen beteiligt.…”
unclassified